2017
DOI: 10.1007/s00280-017-3276-y
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative inhibitory effects of uremic toxins and other serum components on OATP1B1-mediated transport of SN-38

Abstract: Hepatic uptake of SN-38 via OATP1B1 decreases in ESKD patients through cooperative inhibitory effects of UTs and serum components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…), indicating the presence of inhibitors of OATP1B1‐mediated pravastatin uptake in USR. We hypothesized that IS, HA, CMPF, and IAA might cooperatively inhibit OATP1B1‐mediated uptake of pravastatin because a mixture of these UTs at clinically relevant concentrations reportedly inhibited OATP1B1‐mediated SN‐38 uptake . We found that IS, CMPF, and IAA inhibited OATP1B1‐mediated uptake of pravastatin at 30 μM, but not at 300 μM, whereas HA showed an opposite effect (Figs and ).…”
Section: Discussionsupporting
confidence: 92%
“…), indicating the presence of inhibitors of OATP1B1‐mediated pravastatin uptake in USR. We hypothesized that IS, HA, CMPF, and IAA might cooperatively inhibit OATP1B1‐mediated uptake of pravastatin because a mixture of these UTs at clinically relevant concentrations reportedly inhibited OATP1B1‐mediated SN‐38 uptake . We found that IS, CMPF, and IAA inhibited OATP1B1‐mediated uptake of pravastatin at 30 μM, but not at 300 μM, whereas HA showed an opposite effect (Figs and ).…”
Section: Discussionsupporting
confidence: 92%
“…For example, irinotecan undergoes biotransformation by carboxylesterase to the active metabolite SN-38, which is a substrate of hepatic OATP1B1 and is detoxified by glucuronidation. CMPF, indoxyl sulfate, hippuric acid and indole-3-acetic acid competitively inhibit OATP-mediated transport of SN-38 in human hepatocytes and HEK 293 cells [69,85]. Decreased hepatic uptake leads to increased systemic exposure to SN-38 and toxicity.…”
Section: Effects Of Microbial Toxins Beyond Drug Metabolism and Trmentioning
confidence: 99%
“…Drug plasma protein binding has also been shown to be altered in RI due to uremia, hypoalbuminemia and drug interactions with uremic toxins (Keller, Maiga, Neumayer, Lode, & Distler, ; Vanholder, Van Landschoot, De Smet, Schoots, & Ringoir, ). Uremic toxins, many of which are small organic anions such as indoxyl sulfate, can accumulate in renal impairment, and are known substrates of important DTs such as organic anion transporters (OATs), as well as other SLC transporters such as OATP1B1 and ABC transporters (Katsube et al, ; Nigam et al, ). This could result in DDI interactions in renal impairment even when no interaction is expected based on the xenobiotics administered.…”
Section: Discussionmentioning
confidence: 99%